2017
DOI: 10.1097/md.0000000000006424
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of p53 overexpression in squamous cell carcinoma of the sinonasal tract

Abstract: Background:The level of p53 protein expression in sinonasal squamous cell carcinoma (SNSCC) has been estimated, but the results remain inconsistent and the point of consensus has not been reached. This study was first determined to evaluate the clinical effects of p53 expression in SCC of the sinonasal tract.Methods:According to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement criteria, the potential literature was searched from diverse databases. The pooled odds ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A previous study reported that high expression of TrkB plays a major role in SNSCC, and TrkB can be used as a potential prognostic indicator for the clinical prognosis (25). Another report identified that p53 overexpression might be related to the occurrence and development of SNSCC (26). A study by Kovarikova et al (27) suggested that the upregulation of miR-21 was involved in the occurrence and prognosis of sinonasal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that high expression of TrkB plays a major role in SNSCC, and TrkB can be used as a potential prognostic indicator for the clinical prognosis (25). Another report identified that p53 overexpression might be related to the occurrence and development of SNSCC (26). A study by Kovarikova et al (27) suggested that the upregulation of miR-21 was involved in the occurrence and prognosis of sinonasal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The same happens in embryogenesis, where Mdm2 is critically required, and unrestrained p53 activity during development causes early embryonic lethality, as occurs upon loss of the p53-negative regulators Mdm2 or Mdmx [59]. At the same time, as it is known, the overexpression of P53 correlates with carcinogenesis and is an early event in the development of some human carcinomas [60][61][62][63].…”
Section: Permanent Reontogenesis or Rejuvenation Circlementioning
confidence: 90%
“…Vital et al demonstrated an aberrant staining pattern in 60% of their cohort of SCC of the nasal vestibule, which was associated with worse DFS [82]. Wang et al found higher p53 expression in SNSCC compared with benign papillomas and normal mucosa, which was associated with poor to moderate differentiation [83].…”
Section: Novel Biomarkers In Sinonasal Squamous Cell Cancermentioning
confidence: 98%